Effect of Preexisting Musculoskeletal Diseases on the 1-Year Incidence of Fall-related Injuries - Lee, Won Kyung (The Korean Society for Preventive Medicine, 2012)
OBJECTIVES: People who have chronic diseases, as well as gait imbalance or psychiatric drug use, may be susceptible to injuries from falls and slips. The purpose of this study was to evaluate the effect of musculoskeletal diseases on incidental fall-related injuries among adults in Korea. METHODS: We analyzed data from the 4th Korea National Health and Nutrition Examination Survey (2007-2009), which are national data obtained by a rolling survey sampling method. The 1-year incidence of fall-related injuries was defined by health service utilization within the last year due to injury occurring after a slip and fall, and musculoskeletal diseases included osteoarthritis, rheumatoid arthritis, osteoporosis, and back pain. To evaluate the effects of preexisting musculoskeletal diseases, adults diagnosed before the last year were considered the exposed group, and adults who had never been diagnosed were the unexposed group. RESULTS: The weighted lifetime prevalence of musculoskeletal disease was 32 540 per 100 000 persons. Musculoskeletal diseases were associated with a higher risk of fall-related injury after adjustment for sex, age, residence, household income, education, occupation, visual disturbance, paralysis due to stroke, and medication for depression (odds ratio [OR], 1.41; 95% confidence interval [CI], 1.03 to 1.93). As the number of comorbid musculoskeletal diseases increased, the risk of fall-induced injuries increased (p-value for trend <0.001). In particular, patients who had any musculoskeletal condition were at much higher risk of recurrent fall-related injuries (OR, 6.20; 95% CI, 1.06 to 36.08). CONCLUSIONS: One must take into account the risk of fall-related injuries and provide prevention strategies among adults who have musculoskeletal diseases.